Characteristics of powders produced from different parts of sweet potato - Zakaria, Nur Zuriati; Mohd Nor, Mohd Zuhair (Malaysian Society of Agricultural Engineers, 2019)
Sweet potato or scientific name called (Ipomoea batatas (L.) Lam.) is one of the nutritious staple food crops that mostly planted in the tropical regions. Different parts of the sweet potato plant may offer various benefits, but there is a lack of understanding on the properties to link with its potential applications. The objective of this study is to determine the characteristics of powders produced from different parts of sweet potato including stem, leaves, tuber and skin. The analyses were done using powder flow analyser to perform the cohesion test, Powder Flow Speed Dependency test (PFSD test) and caking test. All samples were fixed at 70ml volume for each experiment. The finding showed that the powder of sweet potato stem, leaves, tuber and skin are categorized as free and stable powders and also prone to cake.